2018
DOI: 10.5114/pjr.2018.80207
|View full text |Cite
|
Sign up to set email alerts
|

The utility of ADC measurement techniques for differentiation of low- and high-grade clear cell RCC

Abstract: PurposeTo evaluate the diffusion properties of clear cell renal cell carcinoma (ccRCC) on magnetic resonance imaging (MRI) concerning their Fuhrman nuclear grades and sizes, and to compare the diagnostic performance of two ROI placement techniques for apparent diffusion coefficient (ADC) measurement (entire mass vs. only the darkest region of the mass).Material and methodsFifty-one ccRCC were enrolled in the study and grouped into low-grade ccRCC (Fuhrman grade 1 and 2, n = 37) and high-grade ccRCC (Fuhrman gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
(46 reference statements)
0
1
1
Order By: Relevance
“…In such cases, ADC measurements are taken using different region-of-interest (ROI) placement techniques to distinguish between low and high grade. A study using ADC differentiation by Aslan et al demonstrates an accuracy value of 0.75 whereas our study displays a top accuracy of 0.81 23 . ML-based radiomics methods have potential to enhance differentiation based on grade compared to manual ADC computation.…”
Section: Discussioncontrasting
confidence: 50%
“…In such cases, ADC measurements are taken using different region-of-interest (ROI) placement techniques to distinguish between low and high grade. A study using ADC differentiation by Aslan et al demonstrates an accuracy value of 0.75 whereas our study displays a top accuracy of 0.81 23 . ML-based radiomics methods have potential to enhance differentiation based on grade compared to manual ADC computation.…”
Section: Discussioncontrasting
confidence: 50%
“…Tanaka et al 22 found that high-grade tumors had lower ADC values than low-grade tumors among 91 patients with endometrioid endometrial cancer. Ahmet et al 23 demonstrated that the size and Fuhrman grade of the clear cell renal cell carcinoma were inversely correlated with the ADC value. Yazdani et al 24 showed that significantly lower mean ADC values in high-grade compared to low-grade gliomas.…”
Section: Discussionmentioning
confidence: 99%